Lipid Metabolism at the Nexus of Diet and Tumor Microenvironment - Peck, Barrie; Schulze, Almut (Trends in cancer, 2019)
Obesity is a leading contributing factor to cancer development worldwide. Epidemiological evidence suggests that diet affects cancer risk and also substantially alters therapeutic outcome. Therefore, studying the impact of diet in the development and treatment of cancer should be a clinical priority. In this Review, we set out the evidence supporting the role of lipid metabolism in shaping the tumor microenvironment (TME) and cancer cell phenotype. We will discuss how dietary lipids can impact phenotype thereby affecting disease trajectory and treatment response. Finally, we will posit potential strategies on how this knowledge can be exploited to increase treatment efficacy and patient survival.